Significance of Pyroptosis in Immunoregulation and Prognosis of Patients with Acute Respiratory Distress Syndrome: Evidence from RNA-Seq of Alveolar Macrophages - Liu B; Li Y; Xiang J; Li Y; Zhou M; Ren Y; Fu Z; Ding F (Dove Medical Press, 2023)
Bo Liu,1,2 Yan Li,2,3 Jinying Xiang,2,3 Yuehan Li,2,3 Mi Zhou,2,3 Yinying Ren,2,3 Zhou Fu,2,3 Fengxia Ding2,3 1Department of Cardiothoracic Surgery, Ministry of Education Key Laboratory of Child Development and Disorders, National Clinical Research Center for Child Health and Disorders, China International Science and Technology Cooperation Base of Child Development and Critical Disorders, Children's Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Chongqing Key Laboratory of Pediatrics, Chongqing Engineering Research Center of Stem Cell Therapy, Chongqing Medical University, Chongqing, People's Republic of China; 3Department of Respiratory Medicine, Ministry of Education Key Laboratory of Child Development and Disorders, National Clinical Research Center for Child Health and Disorders, China International Science and Technology Cooperation Base of Child Development and Critical Disorders, Children's Hospital of Chongqing Medical University, Chongqing, People's Republic of ChinaCorrespondence: Fengxia Ding, Department of Respiratory Medicine, Ministry of Education Key Laboratory of Child Development and Disorder, National Clinical Research Center for Child Health and Disorders, China International Science and Technology Cooperation base of Child development and Critical Disorders, Children's Hospital of Chongqing Medical University, No. 136, Zhongshan 2nd Road, Yuzhong Dis, Chongqing, 400014, People's Republic of China, Tel +86-15178712548, Email 482613@hospital.cqmu.edu.cnObjective: This study aimed to investigate the role of pyroptosis in alveolar macrophages regarding the immune microenvironment of acute respiratory distress syndrome (ARDS) and its prognosis.Methods: ARDS Microarray data were downloaded from Gene Expression Omnibus (GEO). Support vector machine (SVM) and random forest (RF) models were applied to identify hub pyroptosis-related genes (PRGs) with prognostic significance in ARDS. RT-PCR was used to detect the relative expression of PRGs mRNA in alveolar macrophages of ARDS mice. Consensus clustering analysis was conducted based on the expression of the PRGs to identify pyroptosis modification patterns. Bioinformatic algorithms were used to study the immune traits and biological functions of the pyroptosis patterns. Finally, protein-protein interaction (PPI) networks were established to identify hub regulatory proteins with implications for the pyroptosis patterns.Results: In our study, a total of 12 PRGs with differential expression were obtained. Four hub PRGs, including GPX4, IL6, IL18 and NLRP3, were identified and proven to be predictive of ventilator-free days (VFDS) in ARDS patients. The AUC values of the 4 PRGs were 0.911 (GPX4), 0.879 (IL18), 0.851 (IL6) and 0.841 (NLRP3), respectively. In ARDS mice, GPX4 mRNA decreased significantly, while IL6, IL18, and NLRP3 mRNA increased. Functional analysis revealed that IL6 had the strongest positive correlation with the CCR pathway, while GPX4 exhibited the strongest negative correlation with the T co-inhibition pathway. Based on the expression of the 4 PRGs, three pyroptosis modification patterns representing different immune states were obtained, and pattern C might represent immune storm.Conclusion: The results showed that pyroptosis plays an important regulatory role in the immune microenvironment of ARDS. This finding provides new insights into the pathogenesis, diagnosis, and treatment of ARDS.Keywords: ARDS, macrophage, pyroptosis, immune, prognosis